Impact of Extreme Rainstorms on Accessibility of Urban Medical Services and Layout Method of Emergency Points: A Case Study of the Shenzhen River Basin - YANG Guang; LIU Yongqiang; LIU Guoqing; LU Wenxiu; FAN Ziwu; LI Suyun; XIAO Zhiming (Renmin Zhujiang)
Under the influence of climate change and the intensifying human activities, extreme rainstorm events occur frequently in urban areas, and flood disasters put forward higher requirements for urban emergency services. This paper selected the Shenzhen River Basin in Shenzhen as the research area. By constructing coupled models of watershed hydrology, one-dimensional hydrodynamics of river network and pipe network, and regional two-dimensional hydrodynamics, it evaluated the urban flood inundation risk under extreme rainstorm conditions and comparatively analyzed the impact of flood inundation on the accessibility of medical services. To maximize the accessible range within 15 minutes after adding new medical service points, an optimization model for the layout and site selection of emergency medical service points was constructed, and a method for arranging emergency medical service points under extreme rainstorm conditions was proposed. The results show that under normal non-rainstorm conditions, starting from the existing 16 emergency medical service points in the Shenzhen River Basin of Shenzhen, any location in the region can be reached within 20 minutes. Under extreme rainstorm conditions, the area that can be reached within 20 minutes accounts for about 80% of the study area. Among them, the main roads in the area near Shennan Middle Road and Shangbu Middle Road are all submerged, directly losing emergency rescue services. In order to control the medical service arrival time at any unsubmerged location in the study area within 15 minutes under extreme rainstorm conditions, emergency service equipment of six community hospitals can be supplemented to optimize emergency service capabilities. After optimization, the average arrival time of emergency services is shortened to less than 5 minutes, which is 2.9 minutes shorter than that of the unoptimized scheme on average. After optimization, the maximum arrival time of emergency services is strictly controlled within 15 minutes, with the maximum travel time being 14.2 minutes, which is 17.2 minutes shorter than the unoptimized time. The addition of six new emergency medical points has significantly improved the accessibility and timeliness of emergency rescue. However, 17% of the study area still cannot obtain timely emergency rescue due to direct flood inundation. In order to effectively solve this problem, it is suggested that for these severely affected areas, the urban flood control and drainage system should be further optimized, and corresponding engineering measures can be adopted to improve drainage capacity. Meanwhile, scientific and reasonable personnel evacuation plans should be formulated to ensure that residents can evacuate quickly and safely when extreme rainfall events occur.